Cover Feature: Atroposelective Synthesis of Isoriccardin C through a C−H Activated Heck Type Macrocyclization (Eur. J. Org. Chem. 9/2021). Issue 9 (23rd February 2021) - Marx, Lisa; Lamberty, Daniel; Choppin, Sabine; Colobert, Françoise; Speicher, Andreas
Abstract : The Cover Feature shows a chiral sulfinyl auxiliary in the ortho ‐position of a biaryl axis inducing a C–H activated atroposelective macrocyclization with final transformation to the configurationally stable natural Isoriccardin C. More information can be found in the Communication by S. Choppin, A. Speicher et al.